PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PURWOSASONO DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , DEWI INDAH HARJANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report explains about surveying and land mapping to produce spatial data information from the Earthâs surface which is then presented in the form of large scale map. Spatial data include point coordinates, spot height, and planimetric detail. The method of measurement used the terrestrial measurement method were using Total Station and Waterpass. Measurement performed included measurement of Horizontal Control Framework (KKH), the measurement of Vertical Control Framework (KKV), and measuremen t of planimetric detail. The result obtained is the situation map presenting the spatial data information on the Earthâs surface area of six location, Purwosasono Hamlet, Beluk Village, Bayat Sub-district, Klaten district, Central Java province by using a scale of scale 1:500 in UTM (Universal Transverse Mercator) pro jection system.